Nine-year analysis of isolated pathogens and antibiotic susceptibilities of microbial keratitis from a large referral eye center in southern China - Lin L; Duan F; Yang Y; Lou B; Liang L; Lin X (Infection and Drug Resistance, 2019)
Lixia Lin,* Fang Duan,* Yao Yang, Bingsheng Lou, Lingyi Liang, Xiaofeng LinZhongshan Ophthalmic Center, State Key Laboratory of Ophthalmology, Sun Yat-sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workPurpose: To analyze the genus profile of isolated pathogens and antibiotic susceptibility trends of microbial keratitis over nine years at a large referral eye center in southern China.Methods: Data of corneal specimens from January 2010 to August 2018 of patients clinically diagnosed with infectious keratitis were obtained from the center’s microbiology database. Results with positive cultures along with antibiotic susceptibility were reviewed and analyzed.Results: We collected and reviewed 7,229 specimens, including 3,092 with positive cultures. Among them, 1,630 (52.72%) were bacterial, 1781 (57.60%) were fungal, and 319 (10.32%) were coinfected. A significant decreasing trend was observed in the isolates of Gram-positive cocci (r =−0.711, P=0.032), among which the proportion of coagulase-negative staphylococcus (CNS) was also reduced (r =−0.883, P=0.002). In contrast, an increasing trend in the proportion of Gram-negative bacilli was observed (r=0.661, P=0.053). The susceptibility rates of Gram-positive cocci to cephalosporins were near 90%, which was relatively high compared to fluoroquinolones. Fluoroquinolones represented the antibiotics to which Gram-negative bacilli were the most susceptible. Their susceptibility to moxifloxacin was 78.79%. The overall performance of aminoglycosides and vancomycin was both around 70%. The susceptibility of Gram-positive cocci to several antibiotics including levofloxacin (r=−0.717, P=0.03), tobramycin (r= −0.933, P<0.001), cefazolin (r= −0.964, P<0.001), ceftazidime (r=−0.929, P=0.003), chloramphenicol (r=−0.929, P=0.003), and cefuroxime (r=−0.829, P=0.042) decreased over time. The susceptibility of Gram-negative bacilli to ofloxacin increased over time (r=0.854, P=0.004), whereas that to cefazolin (r=−0.833, P=0.005) and chloramphenicol (r=−0.886, P=0.019) decreased over time.Conclusion: From 2010 to 2018 in Zhongshan Ophthalmic Center, most isolates from infectious keratitis were Gram-positive cocci (mainly CNS), which decreased over time, with an increase in Gram-positive bacilli. More than half of the antibiotics showed reducing trend of susceptibilities, and the antibiotic resistance situation in southern China was not encouraging.Keywords: infectious keratitis, bacterial keratitis, antibiotic resistance, time trend